Contemporarily used proverbs in SMS messages sent to a Finnish daily paper - Liisa Granbom-Herranen (Portugal, 2022)
Within folkloristic paremiology, proverbs have been regarded mainly as a part of the speech of older people. However, in the new Finnish urban tradition proverbs are not self-evidently passing from generation to generation and they are not anymore taught at school as a part of the curriculum of the native language. Instead, transmission takes place in written form and often within one generation only. Anyhow, the earlier oral tradition has found a place in the colloquial written language. In SMS messages, proverbs are used in a new context, with traditional proverbs occurring alongside the modern ones. Old proverbs are recognisable much more reliably than modern or future ones. Proverbs remain a part of contemporary Finnish communication and everyday language although the context of use has changed over the period which Finnish proverbs have been collected (i.e. over two centuries).